Offspring size and timing of hatching determine survival and reproductive output in a lizard. - Uller, T; Olsson, M (2010)
Selection on offspring size and timing of birth or hatching could have important consequences for maternal investment strategies. Here we show consistent viability selection on hatchling body length across 2 consecutive years in a lizard that lays several clutches per season. There was no effect of hatching date on survival to maturity. However, both early hatching and large hatchling size increased adult size, which has a positive effect on total reproductive output. Earlier hatching also led to an earlier onset of reproduction. Overall, increased survival probability for large hatchlings and a positive effect of clutch size on recruitment suggest consistent directional selection on both egg size and clutch size within and across years. Because offspring size and timing of hatching are strongly affected by environmental and maternal effects, there should be potential for strong transgenerational effects on reproductive output in this species. We briefly discuss the implications of these results for the evolutionary ecology of maternal investment and population fluctuations in short-lived lizards.